Pembuatan Game "Werewolf" pada Mobile Device dengan Near Me menggunakan GPS - Albert Albert; Kartika Gunadi (Jurnal Infra, 2018)
One of the more famous games lately is the Werewolf game. This game requires 15-20 players once a game. In fact, it is very difficult to gather 15-20 players in one place and at the same time. In addition, from existing werewolf game apps, to play with friends around very hard. Therefore, made this Werewolf game with Near Me feature using GPS. Features Near Me itself is a feature that displays a list of game rooms that players are near the user. So the players do not need to spend time looking for the name / game room number to play with. To get the distance from Near Me this is used GPS from each player and will be measured how far distance of player in game room with user use formula to measure distance with latitude and longitude.The steps of making this thesis first is to prepare the game database using MySQL. Then create a game interface using Android Studio, create game server using Firebase. After that, connect the database and game server to Android Studio. Create support features of the game, and do an overall check on the game.The final result of this application is a Werewolf game with features Near Me. After going through several testing phases, this app can be played up to a maximum of 18 players in 1 game room and can have 10 game rooms. Based on the questionnaire results, the Near Me feature was found to facilitate the users in terms of finding the game room when the users were playing together.